Evaluating Digital Inclusion Policy in Local Civil Registration Services: A Case Study of North Kolaka Regency - A. Khusnul Khatimah; Nuryanti Mustari; Ihyani Malik (Lembaga Bale Literasi, 2026)
Digital inclusion policies in public services aim to bridge the digital divide and ensure equitable access to government administrative systems. This study evaluates the effectiveness of the digital inclusion policy implemented through the